Preparation method and application of transition metal modified lithiated zeolite molecular sieve
By using transition metals to modify the lithiated zeolite molecular sieve in the lithium-sulfur battery separator, the rapid attenuation of the cycle capacity and service life caused by the polysulfide shuttle effect and low conductivity of the lithium-sulfur battery is solved, and the cycle stability and discharge specific capacity of the battery are achieved.
Patent Information
- Application Number
- CN202411848776.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-04-18
AI Technical Summary
Lithium sulfur batteries have rapid attenuation of the cycle capacity and service life due to the shuttle effect of polysulfides, low conductivity, insufficient utilization of sulfur and volume changes, which limits their development and application.
By preparing transition metal modified lithiated zeolite molecular sieve and applying it to the separator material of lithium sulfur batteries, it uses its high specific surface area and conductivity to suppress the shuttle effect of polysulfides and improve the reaction kinetics and utilization efficiency of sulfur.
It significantly improves the cycle stability and discharge specific capacity of lithium-sulfur batteries, extends the service life of the battery, and reduces the capacity attenuation rate.
Smart Images

Figure CN119841329A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of fuel cells, and more specifically, relates to a preparation method of a transition metal modified lithiated zeolite molecular sieve and its application. Background Art
[0002] With the global population growth, economic development and technological progress, energy consumption continues to rise. Although the proportion of fossil energy has slightly decreased with the continuous promotion of energy structure transformation, it still accounts for a high proportion of 81.5%. Among them, coal, natural gas and oil have always been the main sources of global energy consumption, accounting for 32%, 26% and 23% respectively. As the world's second largest economy, China's energy consumption is huge, but its consumption still shows obvious disadvantages of imbalance, environmental protection and economy. With the increasing prominence of air pollution and over-exploitation, it is urgent to seek cleaner, greener, safer, more efficient and sustainable solutions. Renewable energy, including solar energy, wind energy, geothermal energy and other new energy sources, has ushered in vigorous development, and solving the problems of production, transportation, efficient storage and conversion and application of renewable energy has gradually been put on the agenda.
[0003] Since the 1990s, the commercialization process of lithium-ion batteries has been continuously developed and improved, and they have been widely used in portable electronic devices such as mobile phones and computers. In recent years, the rapid development of new energy vehicles has also brought the application of lithium-ion batteries to a new level. However, with the growing demand for energy use, the energy density of traditional lithium-ion batteries is only 387Whkg. -1 , which greatly limits its development and application. Due to the ultra-high theoretical energy density of sulfur (2600Wh kg -1 ) and theoretical specific capacity (1675 mAh g -1 ), low-cost benefits brought by the rich raw materials, and non-heavy metal material composition, lithium-sulfur batteries have become the next-generation energy storage technology that is safe and environmentally friendly and has attracted much attention.
[0004] Restricted by the unique electrochemical reaction products of lithium-sulfur batteries, the shuttle effect caused by the dissolution of polysulfides leads to a rapid decay of cycle capacity and service life. The low conductivity of positive electrode sulfur and discharge products Li2S and Li2S2 seriously slows down the kinetics of the electrochemical reaction. At the same time, the dual low problems of sulfur content and effective utilization rate of active substances further affect the battery's cycle and rate performance. The volume change of sulfur during the charging and discharging process reduces the reliability and stability of the battery, hindering the development and application of lithium-sulfur batteries. Summary of the invention
[0005] The present invention firstly provides a method for preparing a transition metal modified lithiated zeolite molecular sieve.
[0006] Secondly, based on the preparation method, a transition metal modified lithiated zeolite molecular sieve was obtained.
[0007] The invention provides again the application of the above transition metal modified lithiated zeolite molecular sieve in lithium-sulfur batteries, especially in lithium-sulfur battery separators.
[0008] The present invention aims at solving the existing technical problems of lithium-sulfur batteries, provides a method for preparing a transition metal-modified zeolite molecular sieve, and uses it as a diaphragm material for lithium-sulfur batteries, which can significantly inhibit the shuttle effect of polysulfides, accelerate the reaction kinetics of sulfur species, and improve the cycle stability of the battery.
[0009] The present invention is achieved through the following technical solutions:
[0010] A method for preparing a transition metal modified lithiated zeolite molecular sieve comprises the following steps:
[0011] S1. Preparation of lithiated zeolite molecular sieve by ion exchange method:
[0012] S11, dissolving 0.5-2 g of lithium chloride in 30-50 ml of water, stirring until uniform to obtain solution A; then grinding 2-3 g of FAU type Y molecular sieve (the FAU type Y molecular sieve can be directly commercially available or homemade) and adding it to solution A to obtain solution B;
[0013] S12, heating and stirring solution B to obtain a uniform solution C after exchange;
[0014] S13, centrifuging the solution C after the reaction to collect the solid product, and drying to obtain a lithiated zeolite molecular sieve material;
[0015] S2. Preparation of transition metal modified lithiated zeolite molecular sieve by ion exchange method:
[0016] S21, dissolving 0.02-0.05 g of molybdenum chloride in 30-50 ml of water to obtain a solution D;
[0017] S22, grinding 0.2-0.5 g of the lithiated zeolite molecular sieve obtained in step S2 finely and adding the mixture to solution D to obtain solution E;
[0018] S23, heating and stirring solution E to obtain solution F;
[0019] S24, centrifuging the solution F after the reaction is completed to collect the solid product, and drying it to obtain the solid product.
[0020] The transition metal modified molecular sieve material provided by the present invention is a porous high specific surface area powder, which is synthesized by a seed-assisted method to obtain a pre-grown molecular sieve gel, and then the gel is transferred to a high-pressure reactor to complete the complete growth of the crystal through a hydrothermal reaction. Then, a double ion exchange including the transition metal is carried out in sequence by an ion exchange method.
[0021] Preferably, the FAU type Y molecular sieve material is prepared by a seed-assisted method, which specifically comprises the following steps:
[0022] S01, dissolve 0.5-1 g of sodium, 1.5-2.5 g of silicon oxide, and 2-3 g of sodium hydroxide in 8-12 ml of water, and continue stirring until uniformly dispersed to obtain Sol A;
[0023] S02, dissolve 0.5-1 g of sodium aluminate, 1.5-2 g of silicon oxide, and 0.5-1 g of sodium hydroxide in 8-12 ml of water, and continue stirring until uniformly dispersed to obtain Sol B;
[0024] S03. Add 0.3-1 g of Sol A aged for 24 hours to Sol B, stir until uniformly dispersed, and age for 24 hours; then transfer the mixed sol to a reactor and react at 80-110°C for 10-14 hours; after the reaction is completed, collect the product by centrifugation and dry to obtain FAU type Y molecular sieve.
[0025] Preferably, in step S12, solution B is heated and stirred at 70-100° C. for 3-6 hours to obtain a uniform solution C after exchange.
[0026] Preferably, in step S23, solution E is heated and stirred at 70-100° C. for 3-6 hours to obtain solution F.
[0027] The present invention simultaneously protects the transition metal modified lithiated zeolite molecular sieve material obtained based on the preparation method.
[0028] Furthermore, the transition metal modified lithiated zeolite molecular sieve material is used in the preparation of lithium-sulfur battery materials.
[0029] Furthermore, the transition metal modified lithiated zeolite molecular sieve material is applied to the preparation of lithium-sulfur battery separators.
[0030] As a specific application, the molecular sieve-CNT composite material can be obtained by simple mixing and grinding and applied to the modification of lithium-sulfur battery separators. For example, the transition metal-modified lithiated zeolite molecular sieve material, carbon nanotubes and a binder are mixed and ground, and then a solvent is added to obtain a slurry, which is coated on the separator and dried to obtain a lithium-sulfur battery separator.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The transition metal modified lithiated zeolite molecular sieve prepared by the present invention has a FAU type molecular sieve as the core, transition metal ions exist in the framework cage, and transition metal ions and lithium ions are distributed on the skeleton structure and outside the framework. When used as a modified diaphragm material for lithium-sulfur batteries, it has the following advantages:
[0033] 1) Material structure advantages. On the one hand, the composite material has both the high specific surface area and porous properties of the molecular sieve material, providing a channel for ion transmission. On the other hand, the molecular sieve's own structural adsorption can effectively adsorb polysulfides and inhibit the diffusion of polysulfides, thereby reducing the negative impact of the shuttle effect.
[0034] 2) Advantages of material properties. FAU molecular sieves have better conductivity than other molecular sieves. Composite with carbon nanotubes further improves the conductivity of the material and accelerates electron transfer. Lithium ions loaded outside the framework can also promote the transfer of lithium. The molecular sieve structure itself has good physical and chemical stability, so it will not react with the electrolyte or be restricted to denaturation. The catalytic active sites within the structure also accelerate the redox reaction kinetics of sulfur, thereby effectively improving the utilization efficiency and discharge specific capacity of the active substance sulfur.
[0035] 3) Transition metal modification advantage. The limited combination of transition metal and skeleton structure largely ensures the stability of the dual synergistic catalytic effect of transition metal and molecular sieve, while the material's adsorption of dissolved shuttle lithium polysulfide ensures the improvement of the conversion process of lithium polysulfide and reduces the large loss of active substances caused by the shuttle effect of lithium polysulfide, thereby affecting the cycle stability. This simultaneous dual process of anchored adsorption-catalytic conversion effectively improves the specific capacity of the battery and reduces the capacity decay rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a front scanning electron microscope image of the transition metal modified lithiated zeolite molecular sieve prepared in Example 1 of the present invention.
[0037] Figure 2 This is a cross-sectional scanning electron microscope image of the transition metal-modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention.
[0038] Figure 3 This is a discharge specific capacity cycle diagram of the transition metal modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention.
[0039] Figure 4 This is a discharge specific capacity rate performance diagram of the transition metal modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The technical scheme of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention and the figures. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are prepared according to the conditions recommended by the normal conditions or the manufacturers. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0041] Example 1: A method for preparing a transition metal modified lithiated zeolite molecular sieve material, comprising the following steps:
[0042] The first step is to prepare FAU type Y molecular sieve material using seed-assisted method:
[0043] Dissolve 0.5 g of sodium aluminate, 2 g of silicon oxide, and 2.7 g of sodium hydroxide in 11 ml of water and continue stirring until uniformly dispersed to obtain Sol A;
[0044] Dissolve 0.5 g of sodium aluminate, 2 g of silicon oxide, and 0.9 g of sodium hydroxide in 11 ml of water, and continue stirring until uniformly dispersed to obtain Sol B;
[0045] 0.7 g of Sol A aged for 24 hours was added to Sol B, stirred until uniformly dispersed, and aged for 24 hours;
[0046] The mixed sol was transferred to a high pressure reactor and reacted at 110°C for 12 hours;
[0047] After the reaction is completed, the product is collected by centrifugation and dried to obtain FAU type Y molecular sieve;
[0048] After testing, the specific surface area of the FAU type Y molecular sieve reached 802.6 square meters per gram.
[0049] The second step is to prepare lithiated zeolite molecular sieve by ion exchange method:
[0050] Dissolve 1.8 g of lithium chloride in 40 ml of water and continue stirring until a uniform solution A is obtained;
[0051] Grind 2 g of the FAU type Y molecular sieve prepared in the previous step and add it to solution A, mix and pre-stir until uniform to obtain solution B;
[0052] Solution B was transferred into a flask, heated and stirred at 80°C for 5 hours to obtain a uniform solution C after exchange;
[0053] After the reaction is completed, the solution C is centrifuged to collect the solid product, and dried to obtain a lithiated zeolite molecular sieve material;
[0054] The third step is to prepare transition metal modified lithiated zeolite molecular sieve by ion exchange method:
[0055] Dissolve 0.04 g of molybdenum chloride in 40 ml of water and continue stirring until a uniform solution D is obtained;
[0056] 0.4 g of the lithiated zeolite molecular sieve prepared in the previous step was finely ground and added to solution D, and the mixture was pre-stirred until uniform to obtain solution E;
[0057] Solution E was transferred into a flask, heated and stirred at 80°C for 4 hours to obtain a uniform solution F after exchange;
[0058] After the reaction is completed, the solution F is centrifuged to collect the solid product, and dried to obtain a transition metal modified lithiated zeolite molecular sieve material;
[0059] An application of a transition metal modified lithiated zeolite molecular sieve material comprises the following steps:
[0060] The prepared transition metal modified lithiated zeolite molecular sieve material, carbon nanotubes and polyvinylidene fluoride were weighed and ground in a mortar according to a mass ratio of 7:2:1 for 1 hour, the ground powder was transferred to a micro weighing bottle, 6 ml of N-methyl-2-pyrrolidone was added, and the mixture was stirred for 4 hours to dissolve evenly to obtain a slurry. The obtained slurry was coated on a polypropylene diaphragm by a doctor blade method, and dried in an oven at 60°C for 12 hours to obtain a transition metal modified lithiated zeolite molecular sieve modified diaphragm, which was used as a lithium-sulfur battery diaphragm material.
[0061] Example 2: A method for preparing a transition metal modified lithiated zeolite molecular sieve material, comprising the following steps:
[0062] The first step is to prepare FAU type Y molecular sieve material using seed-assisted method:
[0063] Dissolve 0.6 g of sodium aluminate, 2.2 g of silicon oxide, and 2.5 g of sodium hydroxide in 10 ml of water, and continue stirring until uniformly dispersed to obtain Sol A;
[0064] Dissolve 0.6 g of sodium aluminate, 2 g of silicon oxide, and 1 g of sodium hydroxide in 10 ml of water, and continue stirring until uniformly dispersed to obtain Sol B;
[0065] 0.4 g of Sol A aged for 24 h was added to Sol B, stirred until uniformly dispersed, and aged for 24 h;
[0066] The mixed sol was transferred into a high pressure reactor and reacted at 80°C for 14 hours;
[0067] After the reaction is completed, the product is collected by centrifugation and dried to obtain FAU type Y molecular sieve;
[0068] The second step is to prepare lithiated zeolite molecular sieve by ion exchange method:
[0069] Dissolve 0.9 g of lithium chloride in 40 ml of water and continue stirring until a uniform solution A is obtained;
[0070] Grind 2 g of the FAU type Y molecular sieve prepared in the previous step and add it to solution A, mix and pre-stir until uniform to obtain solution B;
[0071] Solution B was transferred into a flask, heated and stirred at 90°C for 4 hours to obtain a uniform solution C after exchange;
[0072] After the reaction is completed, the solution C is centrifuged to collect the solid product, and dried to obtain a lithiated zeolite molecular sieve material;
[0073] The third step is to prepare transition metal modified lithiated zeolite molecular sieve by ion exchange method:
[0074] Dissolve 0.02 g of molybdenum chloride in 30 ml of water and continue stirring until a uniform solution D is obtained;
[0075] Grind 0.2 g of the lithiated zeolite molecular sieve prepared in the previous step and add it to solution D, mix and pre-stir until uniform to obtain solution E;
[0076] Solution E was transferred into a flask, heated and stirred at 80°C for 6 hours to obtain a uniform solution F after exchange;
[0077] After the reaction is completed, the solution F is centrifuged to collect the solid product, and dried to obtain a transition metal modified lithiated zeolite molecular sieve material;
[0078] An application of a transition metal modified lithiated zeolite molecular sieve material comprises the following steps:
[0079] The prepared transition metal modified lithiated zeolite molecular sieve material, carbon nanotubes and polyvinylidene fluoride were weighed and ground in a mortar according to a mass ratio of 8:1:1 for 1 hour, the ground powder was transferred to a micro weighing bottle, 5 ml of N-methyl-2-pyrrolidone was added, and the mixture was stirred for 6 hours to dissolve evenly to obtain a slurry. The obtained slurry was coated on a polypropylene diaphragm by a doctor blade method, and dried in an oven at 80°C for 8 hours to obtain a transition metal modified lithiated zeolite molecular sieve modified diaphragm, which was used as a lithium-sulfur battery diaphragm material.
[0080] Example 3: A method for preparing a transition metal modified lithiated zeolite molecular sieve material, comprising the following steps:
[0081] The first step is to prepare FAU type Y molecular sieve material using seed-assisted method:
[0082] Dissolve 0.7 g of sodium aluminate, 2.5 g of silicon oxide, and 2.3 g of sodium hydroxide in 12 ml of water, and continue stirring until uniformly dispersed to obtain Sol A;
[0083] Dissolve 0.5 g of sodium aluminate, 1.7 g of silicon oxide, and 1 g of sodium hydroxide in 12 ml of water, and continue stirring until uniformly dispersed to obtain Sol B;
[0084] Add 0.5 g of Sol B aged for 24 hours, stir until uniformly dispersed, and age for 24 hours;
[0085] The mixed sol was transferred into a high pressure reactor and reacted at 100°C for 13 hours;
[0086] After the reaction is completed, the product is collected by centrifugation and dried to obtain FAU type Y molecular sieve;
[0087] The second step is to prepare lithiated zeolite molecular sieve by ion exchange method:
[0088] Dissolve 1.4 g of lithium chloride in 40 ml of water and continue stirring until a uniform solution A is obtained;
[0089] Grind 2 g of the FAU type Y molecular sieve prepared in the previous step and add it to solution A, mix and pre-stir until uniform to obtain solution B;
[0090] Solution B was transferred into a flask, heated and stirred at 90°C for 3 hours to obtain a uniform solution C after exchange;
[0091] After the reaction is completed, the solution C is centrifuged to collect the solid product, and dried to obtain a lithiated zeolite molecular sieve material;
[0092] The third step is to prepare transition metal modified lithiated zeolite molecular sieve by ion exchange method:
[0093] Dissolve 0.03 g of molybdenum chloride in 30 ml of water and continue stirring until a uniform solution D is obtained;
[0094] 0.15 g of the lithiated zeolite molecular sieve prepared in the previous step was finely ground and added to solution D, and the mixture was pre-stirred until uniform to obtain solution E;
[0095] Solution E was transferred into a flask, heated and stirred at 80°C for 6 hours to obtain a uniform solution F after exchange;
[0096] After the reaction is completed, the solution F is centrifuged to collect the solid product, and dried to obtain a transition metal modified lithiated zeolite molecular sieve material;
[0097] An application of a transition metal modified lithiated zeolite molecular sieve material comprises the following steps:
[0098] The prepared transition metal modified lithiated zeolite molecular sieve material, carbon nanotubes and polyvinylidene fluoride were weighed and ground in a mortar according to a mass ratio of 7:2:1 for 1.5 hours, the ground powder was transferred to a micro weighing bottle, 5 ml of N-methyl-2-pyrrolidone was added, and the mixture was stirred for 5 hours to dissolve evenly to obtain a slurry. The obtained slurry was coated on a polypropylene diaphragm by a doctor blade method, and dried in an oven at 70°C for 10 hours to obtain a transition metal modified lithiated zeolite molecular sieve modified diaphragm, which was used as a lithium-sulfur battery diaphragm material.
[0099] Figure 1 This is a front scanning electron microscope image of the transition metal modified lithiated zeolite molecular sieve prepared in Example 1 of the present invention. It can be seen from the figure that the main grains have completely grown into a complete regular octahedron morphology, and the material prepared in this example can well construct the skeleton structure of the Y-type molecular sieve. At the same time, the lithiation and transition metal modification steps do not damage the material structure, maintaining the integrity of the molecular sieve structure.
[0100] Figure 2 This is a cross-sectional scanning electron microscope image of the transition metal modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention. From the figure, it can be seen that a relatively flat and completely stable cross-sectional morphology is formed. In the case of high-thickness material accumulation, it can still bring good performance improvement. This is attributed to the rich pores and pores formed by the accumulation of the material itself, which constructs a lithium ion transmission pathway and uses the material pore screening characteristics to inhibit the shuttling of lithium polysulfide to a certain extent.
[0101] Figure 3 The discharge capacity cycle diagram of the transition metal modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention is as follows: the lithium-sulfur battery diaphragm material obtained by the implementation of this scheme is cut into 19 mm diameter, and button batteries are assembled in a glove box protected by vacuum argon. The positive electrode sheet, electrolyte, diaphragm, lithium sheet, gasket, and spring sheet of the lithium-sulfur battery are placed in the positive and negative electrode shells in turn, and then taken out for cycle step testing.
[0102] The diaphragm obtained in this embodiment has a first-cycle discharge capacity of 1160 mAh / g at a conventional 0.2C rate current, which is significantly improved compared to the blank diaphragm (about 900 mAh / g). After 100 charge and discharge cycles, it still has a discharge capacity of about 920 mAh / g, while the blank diaphragm is only about 600 mAh / g. Therefore, the modified diaphragm implemented in the present invention can achieve a double improvement in performance in terms of cycle stability and initial discharge capacity.
[0103] The assembled battery is subjected to rate step test. Figure 4 This is a discharge capacity rate performance diagram of the transition metal modified lithiated zeolite molecular sieve modified diaphragm prepared in Example 1 of the present invention. Figure 4It can be shown that the first cycle capacity can reach 1200 mAh / g at a current of 0.1C, and it also shows a good capacity retention rate in a short cycle at the same rate. At a high rate current of 3C, it still has a specific capacity of about 650 mAh / g, and when the low rate is restored, the discharge specific capacity also recovers well. This shows that the diaphragm obtained in this embodiment still has good stability and relatively high discharge specific capacity when facing current changes.
[0104] The above embodiments of the present invention are merely examples for clearly illustrating the technical solution of the present invention, and are not intended to limit the specific implementation methods of the present invention. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the claims of the present invention shall be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a transition metal modified lithiated zeolite molecular sieve, characterized in that: The following steps are involved: S1. Preparation of lithiated zeolite molecular sieve by ion exchange method: S11, dissolving 0.5-2 g of lithium chloride in 30-50 ml of water, stirring until uniform to obtain solution A; then grinding 2-3 g of FAU type Y molecular sieve finely and adding it to solution A to obtain solution B; S12, heating and stirring solution B to obtain a uniform solution C after exchange; S13, centrifuging the solution C after the reaction to collect the solid product, and drying to obtain a lithiated zeolite molecular sieve material; S2. Preparation of transition metal modified lithiated zeolite molecular sieve by ion exchange method: S21, dissolving 0.02-0.05 g of molybdenum chloride in 30-50 ml of water to obtain a solution D; S22, grinding 0.2-0.5 g of the lithiated zeolite molecular sieve obtained in step S2 finely and adding the mixture to solution D to obtain solution E; S23, heating and stirring solution E to obtain solution F; S24, centrifuging the solution F after the reaction is completed to collect the solid product, and drying it to obtain the solid product.
2. The method for preparing the transition metal modified lithiated zeolite molecular sieve according to claim 1, characterized in that: The FAU type Y molecular sieve material is prepared by a seed-assisted method, which specifically includes the following steps: S01, dissolve 0.5-1 g of sodium, 1.5-2.5 g of silicon oxide, and 2-3 g of sodium hydroxide in 8-12 ml of water, and continue stirring until uniformly dispersed to obtain Sol A; S02, dissolve 0.5-1 g of sodium aluminate, 1.5-2 g of silicon oxide, and 0.5-1 g of sodium hydroxide in 8-12 ml of water, and continue stirring until uniformly dispersed to obtain Sol B; S03. Add 0.3-1 g of Sol A aged for 24 hours to Sol B, stir until uniformly dispersed, and age for 24 hours; then transfer the mixed sol to a reactor and react at 80-110°C for 10-14 hours; after the reaction is completed, collect the product by centrifugation and dry to obtain FAU type Y molecular sieve.
3. The method for preparing the transition metal modified lithiated zeolite molecular sieve according to claim 1, characterized in that: In the step S12, the solution B is heated and stirred at 70-100° C. for 3-6 hours to obtain a uniform solution C after exchange.
4. The method for preparing the transition metal modified lithiated zeolite molecular sieve according to claim 1, characterized in that: In the step S23, solution E is heated and stirred at 70-100° C. for 3-6 hours to obtain solution F.
5. A transition metal modified lithiated zeolite molecular sieve material obtained by the preparation method according to any one of claims 1 to 4.
6. Use of the transition metal modified lithiated zeolite molecular sieve material according to claim 5 in the preparation of lithium-sulfur battery materials.
7. The use according to claim 6, characterized in that: The transition metal modified lithiated zeolite molecular sieve material is applied to the preparation of lithium sulfur battery diaphragms.
8. The use according to claim 7, characterized in that: The transition metal modified lithiated zeolite molecular sieve material, carbon nanotubes and a binder are mixed and ground, and then a solvent is added to obtain a slurry, which is coated on a diaphragm and dried to obtain a lithium-sulfur battery diaphragm.